Assessing the performance of maternity care in Europe: a critical exploration of tools and indicators. Issue 1 (June 2015) - Escuriet, Ramón; White, Joanna; Beeckman, Katrien; Frith, Lucy; Leon-Larios, Fatima; Loytved, Christine; Luyben, Ans; Sinclair, Marlene; van Teijlingen, Edwin
Abstract Background This paper critically reviews published tools and indicators currently used to measure maternity care performance within Europe, focusing particularly on whether and how current approaches enable systematic appraisal of processes of minimal (or non-) intervention in support of physiological or "normal birth". The work formed part of COST Actions IS0907: "Childbirth Cultures, Concerns, and Consequences: Creating a dynamic EU framework for optimal maternity care" (2011-2014) and IS1405: Building Intrapartum Research Through Health - an interdisciplinary whole system approach to understanding and contextualising physiological labour and birth (BIRTH) (2014-). The Actions included the sharing of country experiences with the aim of promoting salutogenic approaches to maternity care. Methods A structured literature search was conducted of material published between 2005 and 2013, incorporating research databases, published documents in english in peer-reviewed international journals and indicator databases which measured aspects of health care at a national and pan-national level. Given its emergence from two COST Actions the work, inevitably, focused on Europe, but findings may be relevant to other countries and regions. Results A total of 388 indicators were identified, as well as seven tools specifically designed for capturing aspects of maternity care. Intrapartum care was the most frequently measured feature, through the application of process and outcome indicators. Postnatal and neonatal care of mother and baby were the least appraised areas. An over-riding focus on the quantification of technical intervention and adverse or undesirable outcomes was identified. Vaginal birth (no instruments) was occasionally cited as an indicator; besides this measurement few of the 388 indicators were found to be assessing non-intervention or "good" or positive outcomes more generally. Conclusions The tools and indicators identified largely enable measurement of technical interventions and undesirable health (or pathological medical) outcomes. A physiological birth generally necessitates few, or no, interventions, yet most of the indicators presently applied fail to capture (a) this phenomenon, and (b) the relationship between different forms and processes of care, mode of birth and good or positive outcomes. A need was identified for indicators which capture non-intervention, reflecting the reality that most births are low-risk, requiring few, if any, technical medical procedures.